On seeing information systems as bridges - Bonner, Marcus (School of Management Working Papers, 1995)
The drive in today’s business world is to develop and apply ever faster computers and ever more sophisticated information systems. such a -view is stated in no uncertain terms by Burrows (1986) who maintains that companies must automate in order to survive. Computerized information systems are seen as the saviour to many problems. A local producer of leather products has recently invested half a million New Zealand dollars in a Manufacturing Resource Planning (MRP II) package in the belief that the numerous production problems will be solved by the master production schedule generated by the system. The very real danger this company faces is failure to give full and due consideration to the way it presently organizes it’s business activities in human resource and organizational form terms. Despite the continuing heavy investment in information technology by firms in all business sectors, conflicting results for the impact of IT on organizational performance have been reported (Weill and Olson, 1989 and Weill, 1992). Cragg and King (1992) studied the level of information system sophistication and financial performance of one hundred and twenty (120) computerized small engineering firms in the West Midlands (UK). They found that, for these firms with computers, lower IS sophistication is associated with higher financial performance." (p.424). Despite the limitations noted by Cragg and King, their study sounds a useful warning bell. This paper takes as its basic belief that implementing a computerized information system involves more than merely putting a computer into the organization. It contends that an information system consists of three major elements: people, technology and organizational form. To this end a metaphor is proposed to help understand the relationship and interaction between these three elements. It should be noted that whilst the paper is written from a manufacturing perspective, the proposed metaphor can be applied to other areas of the information systems field.